The moderating role of recovery durations in high-intensity interval-training protocols - Schoenmakers, P. P. J. M.; Hettinga, F. J.; Reed, K. E. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Over recent years, multiple studies have tried to optimize the exercise intensity and duration of work intervals in high-intensity-interval training (HIIT) protocols. Although an optimal work interval is of major importance to facilitate training adaptations, an optimal HIIT protocol can only be achieved with an adequate recovery interval separating work bouts. Surprisingly, little research has focused on the acute responses and long-term impact of manipulating recovery intervals in HIIT sessions. This invited commentary therefore aimed to review and discuss the current literature and increase the understanding of the moderating role of recovery durations in HIIT protocols. Conclusion: The acute responses to manipulations in recovery durations in repeated-sprint training (RST), sprint interval training (SIT), and aerobic interval training (AIT) protocols have recently begun to receive scientific interest. However, limited studies have manipulated only the recovery duration in RST, SIT, or AIT protocols to analyze the role of recovery durations on long-term training adaptations. In RST and SIT, longer recovery intervals (=80 s) facilitate higher workloads in subsequent work intervals (compared with short recovery intervals), while potentially lowering the aerobic stimulus of the training session. In AIT, the total physiological strain endured per training protocol appears not to be moderated by the recovery intervals, unless the recovery duration is too short. This invited commentary highlights that further empirical evidence on a variety of RST, SIT, and AIT protocols and in exercise modalities other than cycling is needed.